2004
DOI: 10.1590/s1519-566x2004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de fungos entomopatogênicos para o controle de Oligonychus yothersi (McGregor) (Acari: Tetranychidae), na cultura da erva-mate (Ilex paraguariensis St. Hill.)

Abstract: Entomopathogenic Fungi Selection to Control Oligonychus yothersi (McGregor) (Acari: Tetranychidae) in Paraguay Tea Crops (Ilex paraguariensis St. Hill.) ABSTRACT-The virulence of strains of the entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae and Paecilomyces fumosoroseus was evaluated on Oligonychus yothersi (McGregor) in laboratory. The bioassays for strain selection and determination of LD 50 and LT 50 were elaborated with leaf disks of Paraguay tea infested with 10 adult females of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
4
0
6
Order By: Relevance
“…Beauveria bassiana and M. anisopliae were pathogenic to T. ogmophallos, which is the first report on the pathogenicity of these fungi to this mite species. Other studies also have reported the pathogenicity of B. bassiana and M. anisopliae to tetranychid species, such as T. urticae (Alves et al 2002;Tamai et al 2002;Shi & Feng 2009;Moro et al 2011), T. evansi (Wekesa et al 2005), T. kanzawai (Sanjaya et al 2013), Mononychellus tanajoa (Bondar) (Acari: Tetranychidae) ( Barreto et al 2004), and oligonychus yothersi (McGregor) (Acari: Tetranychidae) (Oliveira et al 2002(Oliveira et al , 2004.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Beauveria bassiana and M. anisopliae were pathogenic to T. ogmophallos, which is the first report on the pathogenicity of these fungi to this mite species. Other studies also have reported the pathogenicity of B. bassiana and M. anisopliae to tetranychid species, such as T. urticae (Alves et al 2002;Tamai et al 2002;Shi & Feng 2009;Moro et al 2011), T. evansi (Wekesa et al 2005), T. kanzawai (Sanjaya et al 2013), Mononychellus tanajoa (Bondar) (Acari: Tetranychidae) ( Barreto et al 2004), and oligonychus yothersi (McGregor) (Acari: Tetranychidae) (Oliveira et al 2002(Oliveira et al , 2004.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Chandler et al (2000) collected records of 58 fungal species infecting at least 73 mite species. Among fungal entomopathogens, Beauveria bassiana (Balsamo) Vuillemin (Cordycipitaceae) and Metarhizium anisopliae (Metschnikof) Sorokin (Clavicipitaceae) species stand out (Oliveira et al 2004;Lacey 2017;Moro et al 2011). To date, few pathogens have been developed as commercial acaricides due to mass production issues or poor performance under field conditions (Arthurs & Bruck 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The suspensions obtained from each isolate were used according to the highest available conidia per millilitre and are presented in Table 2. These concentrations are based on spore availability and previous references (Dubois et al 2008;Marannino et al 2010;Oliveira et al 2004;Shimazu et al 2002. The suspensions were then stored until use, for less than a week at approximately 5 C.…”
Section: Fungi Culture and Conidia Isolationmentioning
confidence: 99%
“…Com isso, novas ferramentas de manejo de pragas devem ser disponibilizadas aos produtores, como o controle biológico com predadores e patógenos (Polanczyk et al, 2004;collier et al, 2007;Fatoretto et al, 2007), assim como de sua conservação, utilizando agrotóxicos seletivos (Monteiro, 2001;Poletti et al, 2008).…”
unclassified